Designing research: Oppenheim, A N (1992) Questionnaire design, interviewing and attitude measurement. (2nd Edition) London: Pinter Publishers, ISBN 1 85567 044 5 (pbk), pp303, R94.87. ISBN 1 85567 043 7 (hbk). - Collings, Steven J (PINS-Psychology in Society, 2026)
This new edition of Oppenheim's classic text has been revised and updated, as well as expanded to include chapters on research design and sampling, pilot work, questionnaire planning, and statistical analysis. As before, the opening chapters are given over to a practical and down-to-earth introduction to research design. The logic, stages and methodologies of design are outlined in a clear and systematic fashion, and the chapter on descriptive designs has been expanded to include a section on sampling and sampling procedures.